2012
DOI: 10.1111/j.1365-2125.2012.04212.x
|View full text |Cite
|
Sign up to set email alerts
|

Towards the identification of blood biomarkers for acute stroke in humans: a comprehensive systematic review

Abstract: WHAT IS ALREADY KNOWN ABOUT THIS SUBJECTStroke is the largest single cause of disability in the UK. While tests based upon biomarkers have been around for decades, interest in the applications of biomarkers has increased greatly in recent years. Biomarkers released into the bloodstream following a stroke are useful not only for understanding the pathogenesis of stroke, but also play a significant role in the development of personalised medicine. The efficacy of current clinical models and imaging techniques fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
88
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(90 citation statements)
references
References 77 publications
2
88
0
Order By: Relevance
“…There was highly significant difference between the patients and controls regarding CRP which agreed with Hasan et al [19] who found that CRP within 24 h of the onset of the symptoms was significantly differentiated between ischemic stroke and healthy control subjects.…”
Section: Discussionsupporting
confidence: 81%
“…There was highly significant difference between the patients and controls regarding CRP which agreed with Hasan et al [19] who found that CRP within 24 h of the onset of the symptoms was significantly differentiated between ischemic stroke and healthy control subjects.…”
Section: Discussionsupporting
confidence: 81%
“…Another review [3] found C-reactive protein (CRP), P-selectin and homocysteine to differ significantly between ischaemic stroke (in general) and non-stroke controls, but did not assess levels of blood markers between ischaemic stroke subtypes. …”
Section: Introductionmentioning
confidence: 99%
“…Hasan concluded in their report that high levels of glucose were a strong predictor for poor outcome following an ischemic stroke [28]. Another study from 2015 by Masrur found that both acute and chronic hyperglycemia were associated with worse post-stroke outcome, regardless whether diabetes was diagnosed before occurrence of the stroke or not [29].…”
Section: Discussionmentioning
confidence: 99%